ETV6::RUNX1 Acute Lymphoblastic Leukemia: how much therapy is needed for cure - Østergaard, Anna; Fiocco, Marta; de Groot-Kruseman, Hester; Moorman, Anthony V; Vora, Ajay; Zimmermann, Martin; Schrappe, Martin; Biondi, Andrea; Escherich, Gabriele; Stary, Jan; Imai, Chihaya; Imamura, Toshihiko; et al. (Leukemia, 2024)
Recent trials show 5-year survival rates >95% for ETV6::RUNX1 Acute Lymphoblastic Leukemia (ALL). Since treatment has many side effects, an overview of cumulative drug doses and intensities between eight international trials is presented to characterize therapy needed for cure. A meta-analysis was performed as a comprehensive summary of survival outcomes at 5 and 10 years. For drug dose comparison in non-high risk trial arms, risk group distribution was applied to split the trials into two groups: trial group A with ~70% (range: 63.5-75%) of patients in low risk (LR) (CCLSG ALL2004, CoALL 07-03, NOPHO ALL2008, UKALL2003) and trial group B with ~45% (range: 38.7-52.7%) in LR (AIEOP-BFM ALL 2000, ALL-IC BFM ALL 2002, DCOG ALL10, JACLS ALL-02). Meta-analysis did not show evidence of heterogeneity between studies in trial group A LR and medium risk (MR) despite differences in treatment intensity. Statistical heterogeneity was present in trial group B LR and MR. Trials using higher cumulative dose and intensity of asparaginase and pulses of glucocorticoids and vincristine showed better 5-year event-free survival but similar overall survival. Based on similar outcomes between trials despite differences in therapy intensity, future trials should investigate, to what extent de-escalation is feasible for ETV6::RUNX1 ALL.
Keywords: fúzní onkogenní proteiny; míra přežití; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; protein PEBP2A2; ETS Translocation Variant 6 Protein; Repressor Proteins; Antineoplastic Combined Chemotherapy Protocols; protein ETS, translokační varianta 6; Core Binding Factor Alpha 2 Subunit; Survival Rate; Oncogene Proteins, Fusion; represorové proteiny; protokoly protinádorové kombinované chemoterapie; akutní lymfatická leukemie; lidé; protoonkogenní proteiny c-ets